1996
DOI: 10.1073/pnas.93.10.5111
|View full text |Cite
|
Sign up to set email alerts
|

The cloned rat pancreatic polypeptide receptor exhibits profound differences to the orthologous receptor.

Abstract: Pancreatic polypeptide (PP) is produced in the islets of Langerhans and released in response to meals. It belongs to a family of peptides that also includes neuropeptide Y and peptide YY. In the present communication, we describe a rat receptor with high affinity for PP, therefore named PP1. Clones for the PP1 receptor were obtained by PCR using sequence information for the neuropeptide Y receptor Y1 from several species. The PP1 receptor has 46% overall amino acid sequence identity to the rat Y1 receptor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 35 publications
(30 reference statements)
2
65
0
Order By: Relevance
“…Y n -R were identified (see Larhammar, 1996;Michel et al, 1998 for reviews): Y 3 -R (Herzog et al, 1993), Y 4 -R (Lundell et al, 1996), Y 5 -R (Hu et al, 1996;Haynes et al, 1998, the "food intake" receptor), and Y 6 -R (Weinberg et al, 1996). In addition, it is noteworthy that several studies have suggested that NPY may be one of the endogenous ligands of receptors (Roman et al, 1989).…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 99%
“…Y n -R were identified (see Larhammar, 1996;Michel et al, 1998 for reviews): Y 3 -R (Herzog et al, 1993), Y 4 -R (Lundell et al, 1996), Y 5 -R (Hu et al, 1996;Haynes et al, 1998, the "food intake" receptor), and Y 6 -R (Weinberg et al, 1996). In addition, it is noteworthy that several studies have suggested that NPY may be one of the endogenous ligands of receptors (Roman et al, 1989).…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 99%
“…They are heptahelical G protein-coupled receptors and are referred to as Y receptors (Michel et al, 1998). Y 1 , Y 2 , and Y 5 receptors have similar affinity to NPY and PYY, whereas Y 4 receptor seems to be specific for PP (Voisin et al, 2000) although there was initial confusion regarding its pharmacological profile (Bard et al, 1995;Lundell et al, 1995Lundell et al, , 1996Yan et al, 1996). A Y 6 receptor has been cloned in mice (Weinberg et al, 1996) but seems to be absent in rats (Burkhoff et al, 1998).…”
mentioning
confidence: 99%
“…The integrity of Figure 1 Amino acid sequence alignment made using the Lasergene DNASTAR Megalign software. The chY4 receptor serves as master sequence in alignment with human (Lundell et al 1995), guinea pig (Eriksson et al 1998), pig , rat (Lundell et al 1996) and mouse (Gregor et al 1996) Y4 receptors. Dashes represent gaps introduced to optimise alignment.…”
Section: Localisation Of Receptor Mrna By Rt-pcr and In Situ Hybridismentioning
confidence: 99%
“…In mammals, the affinity of pancreatic polypeptide for this receptor is much greater than the affinities of NPY and PYY (Bard et al 1995, Lundell et al 1995, 1996, Gregor et al 1996. The rat receptor is even more selective for pancreatic polypeptide than are the human and guinea pig receptors (Lundell et al 1996, Eriksson et al 1998. In mammals, the Y4 receptor has a modest neuronal expression in the paraventricular nucleus and in the brainstem (Dumont & Quirion 2000, Larsen & Kristensen 2000, but has a wider peripheral expression in the gut, which agrees well with the role of pancreatic peptide in regulating gastrointestinal functions (Hazelwood 1993, Voisin et al 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation